Notes on the Avifauna of the Balinsasayao Rainforest Region, Negros Oriental, Philippines - Erickson, Keith R.; Heideman, Paul D. (Silliman Journal, 2024)
Fifty species of birds were recorded within a 300ha watershed that lies within approximately 2400ha of primary forest in the mountains of Southern Negros. Thirteen of those species had not been recorded previously at the site; a total of 114 species of birds have now been recorded at the site. An immature male Zoothera andromedae is the first specimen of that species taken on the island of Negros.